Arthur Miller : a critical study - Bigsby, C. W. E. (Cambridge University Press, 2005)
Drawing on extensive interviews and rehearsal material, Christopher Bigsby explores the entirety of Arthur Miller's work (plays, poetry, fiction and films) up to the present in this comprehensive and stimulating study. This is an enjoyable insight into a great playwright that will interest both theatregoers and students of modern drama.